Kuat Tekan Beton Fc’19 Mpa Menggunakan Campuran Styrofoam - Telly - Rosdiyani; Syahri Syahri (Faculty of Engineering, Kadiri University, 2021)
The selection of concrete constituent materials is something to note, considering that it affects the quality and weight of concrete types. The high density of concrete makes the dead load on the structure large. Styrofoam in the concrete mixture will form cavities, thus reducing the overall weight of concrete and light concrete forms with a smaller volume weight. This study aims to find out the effect of the addition of Styrofoam to the compressive strength and strong bending of concrete. Percentage increase of 0%,5%, 15%, 30% of concrete volume with a sample count of 3 pieces for each variation Methods used experimental methods and literature studies. Test results at a concrete age of 28 days showed that the highest compressive strength obtained at a percentage of 5% of 17.78 MPa and a bending force of 2.32 Mpa. A variation of 30% obtained a compressive strength of 12.97 Mpa and bending strength of 1.98 Mpa with a volume weight of 1881.25 kg/m3 in the categories light concrete. So the greater the addition of Styrofoam, the lower the value of compressive strength and strong bending produced. With that percentage (30%), it is recommended for non-structural buildings in indoor conditions.